Solid Wastes Management of Monastery by Circular Economy: Case Studies of Chakdang and Suankeaw Temples in Thailand - Pannaracha, Pitsanu; Teyarachaakul, Mayuree; Kreetachat, Torpong; Wirojanagud, Wanpen (International Journal of Integrated Engineering, 2025)
Along with the natural uses for production and consumption; various waste types, particularly solid wastes have been massively increased. Municipal solid waste is one of the critical generating solid wastes.  Monastery, as one type of municipal solid wastes generating sources, has been rarely justified for solid waste management. This paper is to present solid wastes management of the Monastery using circular economy (CE) concept. The study monasteries included Chakdang and Suankeaw Temples in Thailand. Both temples have carried out solid wastes management on CE approach, 5 Rs (Reduction, Repair, Recycle, Reuse, Refurbish), but different in some Rs implementation. Chakdang Temple has emphasized recycle processing particularly plastic bottles recycled to fibres to proceed for yellow robe for monk, blanket, T-shirt, etc; biodegradation of food wastes to fertilizer by digestion tank, composting of plant residue to fertilizer, conversion of plastic bags and plastic straws to gasoline by pyrolysis.  The CE approaches were mainly reduction through separation together with recycle, and some repair and refurbish. While Suankeaw Temple has used the donated items (mostly electric items and furniture including televisions, refrigerators, fans, computers, beds, wardrobes, chairs, tables, etc) for solid wastes processing through separation and selling to the old goods retailing shops by auction; bio-degradation of animal excreta wastes to earthworm-fertilizer as well as bio-degradation of food wastes, agricultural residue mixed with human excreta and animal manure to fertilizer. The approach was mainly reduction together with repair, and some refurbish. The outcome of the Circular Economy approach in terms of value addition on recycle and repair solid wastes were approximately 0.3 Million US$ a year for Chak Dang Temple, and 15 Million US$ a year for Suan Kaew Temple.    For both monasteries has been attained Sustainable Development Goal. The research also studied for the factors influencing towards Resulted Base Management.  Leader and leadership of the abbots of both temples are the main factors influencing the people to cooperate for solid wastes management by CE approach.